2014
DOI: 10.4103/2141-9248.139358
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum lipids in women with pre-eclampsia

Abstract: Background:Evidence of increased oxidative stress due to endothelial dysfunction in pre-eclampsia has been well-established. Increase in the oxidative stress is associated with abnormal lipid profile.Aim:The aim of the study is to compare serum lipids in pre-eclamptic women and healthy pregnant women.Subjects and Methods:In this case-control study, blood samples were collected from 40 pregnant females diagnosed as pre-eclampsia and 80 normal pregnant females at the Department of Obstetrics and Gynecology at Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
5
18
0
1
Order By: Relevance
“…which was sta s cally significant with p <0.001. This was 24 consistent with the studies done by A Siddiqui and Ghaffar 25 et.al. indica ng the implica on of raised serum triglyceride levels in the pathogenesis of pre-eclampsia.…”
supporting
confidence: 93%
“…which was sta s cally significant with p <0.001. This was 24 consistent with the studies done by A Siddiqui and Ghaffar 25 et.al. indica ng the implica on of raised serum triglyceride levels in the pathogenesis of pre-eclampsia.…”
supporting
confidence: 93%
“…Increased TG in pre-eclampsia are likely to be deposited in uterine spiral arteries and contribute to the endothelial dysfunction, both directly and indirectly through generation of small, dense LDL. 14 In present study, serum VLDL level increased significantly in PIH, and this is in accordance with the study done by Jayanta De et al The increase in the VLDL value is perhaps due to hypertriglyceridemia leading to enhanced entry of VLDL that carries endogenous triglyceride into circulation. 15 Sattar et al 16 reported no significant alteration in TC level whereas in our study statistically significant increase was seen in TC level in PIH women than in control group.…”
Section: Resultssupporting
confidence: 93%
“…Twenty‐seven studies reported on HDL levels,32, 37, 41, 44, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74 of which 24 studies could be included in a meta‐analysis 32, 37, 41, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72. HDL level was lower in pre‐eclampsia than in controls (mean difference −6.29 mmol/L; 95%CI −9.74−2.85; P  = 0.0003) with the strongest effect in subgroup analysis for severe pre‐eclampsia vs. controls ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies reported on HDL levels, 32,37,41,44, of which 24 studies could be included in a metaanalysis. 32,37,41,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] HDL level was lower in pre-eclampsia than in controls (mean difference À6.29 mmol/L; 95%CI À9.74À2.85; P = 0.0003) with the strongest effect in subgroup analysis for severe pre-eclampsia vs. controls (Figure 4).…”
Section: High-density Lipoproteinmentioning
confidence: 99%